2010
DOI: 10.4097/kjae.2010.58.5.450
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness of the streamlined liner of pharyngeal airway (SLIPA™) compared with the laryngeal mask airway ProSeal™ during general anesthesia

Abstract: BackgroundThe aim of this study was to compare the streamlined liner of the pharynx airway (SLIPA), a new supraglottic airway device (SGA), with the laryngeal mask airway ProSeal™ (PLMA) during general anesthesia.MethodsSixty patients were randomly allocated to two groups; a PLMA group (n = 30) or a SLIPA group (n = 30). Ease of use, first insertion success rate, hemodynamic responses to insertion, ventilatory efficiency and positioning confirmed by fiberoptic bronchoscopy were assessed. Lung mechanics data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 29 publications
4
48
3
Order By: Relevance
“…Of the fourteen included randomised controlled trials , one study was a randomised crossover study . Two studies had been prospectively registered .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the fourteen included randomised controlled trials , one study was a randomised crossover study . Two studies had been prospectively registered .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies had been prospectively registered . The SLIPA was compared with the classic LMA in seven studies , with the ProSeal LMA in six , and with the SoftSeal LMA in one . Three studies compared the SLIPA with two other types of airway device , namely: with the classic LMA and the i‐gel ™ ; with the classic LMA and a tracheal tube ; and with the ProSeal LMA and a tracheal tube .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heel of the SLIPA TM is placed in the nasopharynx, providing an additional seal that increases leak pressure. Previous studies have demonstrated that the leak pressure of SLIPA TM (reported means were 27, 1 24, 4 and 30 cm H 2 O) 5 is greater than that of other LMADs (23 cm H 2 O). 2 In conclusion, we believe that SLIPA TM may be more effective than LMAD in difficult airway management, especially in patients whose pharyngeal space is narrow and in whom the PIP is high.…”
Section: To the Editormentioning
confidence: 87%
“…The streamlined liner of the pharynx airway (SLIPA TM ) is a non-cuffed single-use SGA, its shape is designed to stick to the pharynx and palate [2,3]. The shape of SLIPA TM has a hollow body which allows it to fit in the patient's pharynx, sealing it without the use of an inflatable cuff.…”
Section: Introductionmentioning
confidence: 99%